KELALAIAN NOTARIS MENGELUARKAN SALINAN KETIKA MINUTA AKTA BELUM DI TANDA TANGANI (STUDI KASUS PUTUSAN PENGADILAN NEGERI KISARAN NOMOR 657/PID.B/2015/PN.KIS) - RAHMAT HASAN ASHARI HASIBUAN (PREMISE LAW JURNAL, 2017)
The issuance of a copy before the signing of the draft by the persons appearing is invalid and is not in accordance with its procedure. The result of the research shows that the issuance of the copy of a deed before its draft is signed is violating the image of the professionalism of a Notary as a public official in drawing up authentic deeds as complete and strong evidence. A Notary’s liability for the issuance of the copy of deeds when the minute deed is not signed, in this case, can be viewed from two aspects: the aspect of liability based on the Notarial Act and the Notarial Act. It is recommended that a Notary, in his job to make authentic deeds, understand well, correctly, and carefully in drawing up a deed so that it does not lose its authenticity and harm other people. Keywords: Notary’s Negligence, Copy of Deed, Deed Minuta